Pensamiento y lenguaje - Luque Moreno, Lilian Mariantonieta (2020)
The session titled Thought and Language corresponding to the Area of Civic and Citizenship Personal Development for students in the second grade of secondary school at the Good Pastor Educative Institution has been developed taking into account the guidelines in the NCD. The purpose of the session is for the students to know or identify the basic elements and functions of thinking and their relation with the language. The constructivist focus was taken into account and its respective strategies, the thematic field was based on the theorical contributions from the authors of general psychology.